SCIENTIFIC LANGUAGE AS DETERMINATION FACTOR OF THE STATE SELF-IDENTITY - Kozyrski, W. G.; Shenderovskyj, V. A. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
The estimated role of scientific Ukraine language is reflected in the life of the state and society. Short historical analyze for this gives the row of no passing lessons.